Diagnostic Accuracy of Abdominal wall Ultrasonography and Local Wound Exploration in Predicting the Need for Laparotomy following Stab Wound - Ali Vafaei; Kamran Heidari; Afshin Saboorizadeh; Amin Shams Akhtari (Emergency, 2016)
Introduction: Screening of patients with anterior abdominal penetrating trauma in need for laparotomy is an important issue in management of these cases. This study aimed to compare the accuracy of abdominal wall ultrasonography (AWU) and local wound exploration (LWE) in this regard. Methods: This diagnostic accuracy study was conducted on ≥ 18 year-old patients presenting to emergency department with anterior abdominal stab wound and stable hemodynamics, to compare the characteristics of AWU and LWE in screening of patients in need of laparotomy. Results: 50 cases with the mean age of 28.44 ± 7.14 years were included (80% male). Sensitivity, specificity and area under the receiver operating characteristic (ROC) curve of AWU were 70.58 (95% CI: 44.04 – 88.62), 93.33 (95% CI: 76.49 – 98.83), and 81.96 (95% CI: 69.91 – 94.01), respectively. These measures were 88.23 (62.25 – 97.93), 93.33 (76.49 – 98.83), and 90.78 (95% CI: 81.67 – 99.89) for LWE, respectively. The difference in overall accuracy of the two methods was not statistically significant (p = 0.0641). Conclusion: Based on the findings of the present study, AWU and LWE had the same specificity but different sensitivities in screening of anterior abdominal stab wound patients in need of laparotomy. The overall accuracy of LWE was slightly higher (91.48% versus 85.1%).